Oxidative stability of walnut (Juglans regia L.) and chia (Salvia hispanica L.) oils microencapsulated by spray drying - Martinez, Marcela Lilian (2014)
his work was primarily aimed to evaluate the use of maltodextrin in combination with hydroxypropyl methylcellulose as wall materials for microencapsulation of both walnut and chia oils by spray drying. The effect of rosemary extract on the oxidative stability of the microencapsulated oils was examined under prolonged storage conditions. After a 45-day storage, the microencapsulated chia oil with rosemary extract showed lower formation of primary oxidation compounds than the control without additives, highlighting a protective effect of the antioxidant. Nevertheless, during the entire storage period the unencapsulated chia oil reported lower oxidative damage than their encapsulated counterparts, showing that the spray drying process affected its stability negatively. Walnut oil microencapsulation protected the oil from oxidation in comparison with its unencapsulated counterpart which was further apparent from the 30th day of storage. The addition of 1600 ppm of rosemary extract effectively protected microencapsulated walnut oil, showing – throughout the storage period – lower oxidation values in comparison with its analogous unencapsulated oil. The microcapsule surface oil and the images obtained by scanning electron microscopy at the beginning and at the end of the assay showed that the wall material has not been altered during storage.